The Role Of Strategic Leadership In Achieving Institutional Excellence At The Ministry Of Interior In The United Arab Emirates: The Modern Management As An Intermediate Variable - Salem Mehmas Awad Alshamsi; Ibrahim Fahad Sulaiman (OCERINT- International Organization Center of Academic Research, 2024)
Volume: 8 Issue: 24 (page : 722 - 741)